Proteomics: a tool to develop novel diagnostic methods and unravel molecular mechanisms of pediatric diseases - Angélica Torres-Arroyo; Arturo Ruiz-Lara; Adriana Castillo-Villanueva; Sara Teresa Méndez-Cruz; Sara Elvia Espinosa-Padilla; Francisco Javier Espinosa-Rosales; Flora Zarate-Mondragón; Roberto Cervantes-Bustamante; Vanessa Bosch-Canto; Iris Vizzuett-López; Juan Carlos Ordaz-Fávila; Jesús Oria-Hernández; et al. (Permanyer, 2017)
Proteomics is the study of the expression of changes and post-translational modifications (PTM) of proteins along a metabolic condition either normal or pathological. In the field of health, proteomics allows obtaining valuable data for treatment, diagnosis or pathophysiological mechanisms of different illnesses. To illustrate the aforementioned, we describe two projects currently being performed at the Instituto Nacional de Pediatría: The immuno-proteomic study of cow milk allergy and the Proteomic study of childhood cataract. Cow's milk proteins (CMP) are the first antigens to which infants are exposed and generate allergy in some of them. In Mexico, the incidence of CMP allergy has been estimated at 5-7%. Clinical manifestations include both gastrointestinal and extra-gastrointestinal symptoms, making its diagnosis extremely difficult. An inappropriate diagnosis affects the development and growth of children. The goals of the study are to identify the main immune-reactive CMP in Mexican pediatric population and to design more accurate diagnostic tools for this disease. Childhood cataract is a major ocular disease representing one of the main causes of blindness in infants; in developing countries, this disease promotes up to 27% of cases related to visual loss. From this group, it has been estimated that close to 60% of children do not survive beyond two years after vision lost. PTM have been pointed out as the main cause of protein precipitation at the crystalline and, consequently, clouding of this tissue. The study of childhood cataract represents an outstanding opportunity to identify the PTM associated to the cataract-genesis process.